2014
DOI: 10.1002/stem.1799
|View full text |Cite
|
Sign up to set email alerts
|

Type II Interferon Promotes Differentiation of Myeloid-Biased Hematopoietic Stem Cells

Abstract: Interferon gamma (IFNγ) promotes cell division of hematopoietic stem cells (HSCs) without affecting the total HSC number. We postulated that IFNγ stimulates differentiation of HSCs as part of the innate immune response. Here we report that type II interferon signaling is required, both at baseline and during an animal model of LCMV infection, to maintain normal myeloid development. By separately evaluating myeloid-biased and lymphoid-biased HSC subtypes, we found that myeloid-biased HSCs express higher levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
113
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 37 publications
5
113
1
Order By: Relevance
“…30 We thus measured the serum IFNa concentration in miR-22 KO and WT animals on day 3 following infection. Notably, WT animals mounted a strong IFNa response, while the IFNa levels in miR-22 KO were significantly lower (Figure 2C) 29 . Additionally, miR-22 KO animals demonstrated no baseline elevation in IFNa and no induction of IFNa at day 6 post-infection (Figure 2C, data not shown).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…30 We thus measured the serum IFNa concentration in miR-22 KO and WT animals on day 3 following infection. Notably, WT animals mounted a strong IFNa response, while the IFNa levels in miR-22 KO were significantly lower (Figure 2C) 29 . Additionally, miR-22 KO animals demonstrated no baseline elevation in IFNa and no induction of IFNa at day 6 post-infection (Figure 2C, data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…MicroRNAs are frequently devoid of phenotypes in absence of stress, therefore we next compared peripheral blood immune cell numbers in miR-22 KO versus WT mice 6 days after a non-lethal short-term LCMV infection which is near the peak of response in blood 29 . Notably, platelets were depleted in WT animals during LCMV infection but not in miR-22 KO animals (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that IFNγ stimulates cell division of HSCs in a murine model of Mycobacterium avium infection, leading to a defect in repopulation capacity (Baldridge et al, 2010). Furthermore, short-term IFNγ-mediated HSC division appears to accelerate differentiation during infection (Matatall et al, 2014); however, both the long-term impact and the mechanism of these processes remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…IFN stimulation leads to increased proliferation and differentiation of hematopoietic progenitors, suggesting a role for stem cells in building the army of immune cells needed to respond to microbial invasion and injury (Matatall et al, 2014). Unlike the antiviral state in the affected tissue, these interferon responses occur remote from the site of infection and are not associated with immediate apoptosis or induction of cytotoxic responses.…”
mentioning
confidence: 99%